Correlation Between Visfatin, Insulin Resistance (Homeostasis Model Assesment of Insulin Resistance), Inflammation (High Sensitivity C-Reactive Protein) and HDL Cholesterol Concentration in Individuals with Visceral Obesity - Rini Budiyati; Widjaja Lukito; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Visfatin is a novel adipokine secreted from visceral adipose tissue and has insulinomimetic properties. Visceral obesity is a risk factor for metabolic syndrome. Insulin resistance and inflammation are linked to visceral obesity and metabolic syndrome. Dysregulation of visfatin as an adipokine could play an important role in metabolic syndrome through insulin resistance and inflammation, or lower HDL cholesterol concentration. However, this need more evidence.METHOD: This was a crossectional study in 40 Indonesian obese men and 40 Indonesian obese women. Age: 30-60 years in men and 50-60 years for women, from February to March 2008 in Jakarta.RESULTS: No correlation between visfatin and hs-CRP as a marker of inflammation (r=0.190, p=0,101), or HOMA-IR as a marker of insulin resistance (r=-0.020, p=0.246). Suprisingly visfatin concentration is correlated with HDL Cholesterol (r=0.416, p=0.000).CONCLUSIONS: Visfatin plays an important role in metabolic syndrome through lipid metabolism. Positive correlation between visfatin and HDL cholesterol, was assumed that visfatin had a protective effect. Visfatin also known as as nicotinamide phosphoribosyltransferase (NAMPT) links Nicotinamide Adenine Dinucleotide (NAD) metabolism and raising of HDL Cholesterol. But the exact mechanisms need to be further studied.KEYWORDS: visceral obesity, metabolic syndrome, NAMPT, visfatin, HDL